The symbolic meaning of the Sandeq boat making process among the Mandarese - Sonni, Alem Febri; Amrullah, Muhammad; Bahfiarti, Tuti (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
This article aims to explain the symbolic meaning in the process of making the traditional sandeq boat of the Mandar people. The data collection process was carried out from April to June 2017. Data were obtained through in-depth interviews with 6 purposively selected expert informants, as well as direct observation in the field. The results of this study indicate that the ritual that accompanies the making of the traditional sandeq boat is seen in three main stages, namely: at the beginning of boat building, in the process of making boats, and launching boats into the sea. The meaning contained in the implementation of the ritual is the hope that it will always be given safety in using the boat. In addition, the ritual also intends to ask for abundant sustenance from the process of going to sea later. The religious value of the Mandar people is clearly seen from every stage of the ritual carried out, using mantras and prayers as verbal messages adopted from the Quran and with Islamic nuances. In addition, nonverbal messages in the ritual of making sandeq boats are centered on the use of ussul or the knowledge system of the local community which is carried out with actions or symbolic objects to show their hopes or desires.